Hambatan Komunikasi Antar Budaya Mahasiswa Asing Universitas Teknologi Sumbawa - Ahmad Roja Dhiyaul Haq (Universitas Katolik Widya Karya Malang, 2023)
Communication is a natural way for humans to convey ideas, identity, ideas and their existence to others. One type of communication is intercultural communication. This is communication that occurs between communication participants who have different cultural backgrounds. Sumbawa University of Technology is a tertiary institution that has foreign students from various countries in the world, it is this condition that makes Cross-Cultural Communication intertwined here. The purpose of this research is to find out the barriers to cross-cultural communication experienced by foreign students at the Sumbawa University of Technology. This research is categorized as a qualitative research with data collection techniques, namely interviews. Three informants have become participants in this study who were selected based on a purposive sampling technique. Furthermore, data were analyzed using the Milles & Huberman model with 3 stages; data reduction, data presentation, and conclusions. The results of this study indicate that the barriers to Cross-Cultural Communication experienced by foreign students at the Sumbawa University of Technology are language, misunderstanding of nonverbal behavior, a tendency to judge, and high anxiety.